Islamic Education Teachers' Role in Enhancing ‎Aesthetic Values as Viewed by Secondary School ‎Students in the State of Kuwait - Al-Kandari, Aisha; El-Shara’‎, Ibrahim (Jordan Journal of Educational Sciences, 2023)
This study sought to determine, from the perspective of the students, how Islamic education teachers in the State of Kuwait might improve secondary students' aesthetic values. A stratified random sample of 1610 students was chosen. A descriptive survey design was employed. The validity and reliability of an instrument consisting of 75 items were established. The results showed that the students gave high marks to the role of Islamic education teachers in helping them develop their aesthetic values, with the faith domain receiving the highest marks, followed by worship, ethics, and transactions. There were statistically significant differences (α =0.05) in their estimation of the degree of teaching level in favor of the students in the twelfth grade, but there were no statistically significant differences regarding gender or school type. In light of the findings (p=0.05), the researchers suggested that secondary-level Islamic education textbooks should include a section on aesthetic values